Mid-infrared optical coherence tomography as a method for inspection and quality assurance in ceramics additive manufacturing - Ivan Zorin; Dominik Brouczek; Sebastian Geier; Serkan Nohut; Julia Eichelseder; Guillaume Huss; Martin Schwentenwein; Bettina Heise (Open Ceramics, 2022)
In the past decade, significant progress has been made in ceramics additive manufacturing (AM). Material research and the rapid evolution of high-resolution printing technologies enabled the production of high-quality, high-precision, complex-structured ceramic objects. In this contribution, we propose a contactless, non-destructive method of mid-infrared optical coherence tomography (mid-IR OCT) for at-line inspection and quality assurance of AM ceramics. The OCT system operates in the spectral range from 3.15 μm to 4.2 μm featuring extended probing depth into porous ceramics. The spatial resolution of the mid-IR OCT system is suited to most of AM techniques: the axial resolution (determined by the coherence length) is 8 μm; the lateral resolution is around 40 μm (determined by the size of the focused beam). The capabilities of the method are demonstrated by imaging diverse high-scattering single and multi-component samples (in both green and sintered states) fabricated by means of lithography-based ceramics manufacturing. The selected materials are alumina and zirconia, the gold standard in AM. Some features of interest, such as local changes in porosity, surface and sub-surface defects and layer structure, were accessed and analyzed.